Emotional-social competencies that enhance wellness in teachers: an exploratory study - Van Wyk, Mirna F. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MEdPsych (Educational Psychology))--University of Stellenbosch, 2006.